Cassava: a resilient crop with great potential - International Center for Tropical Agriculture (2014)
Did you know that demand for dried cassava is increasing for livestock feed, industry and biofuel? Cassava is a resilient, climate-smart crop. 1/3 of the world production is grown in Asia.